Accelerated synchronization in system with SSS (spread spectrum signal) with optimized structure - Andonov, Antonio; Dimkin, Petar; Mihova, Mariana (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
In the systems with spread spectrum signal the quasi-coherent acceptance can not be made without prior synchronization, because in the real conditions the phase, position of time and Doppler shift frequency are unknown. For the purposes of processing of quasi-coherent SSS should make the introduction of tracking devicesin step with an accuracy determined by the area of the grip devices. The accuracy of determining the frequency and the delay of the received signal must be determined by the appropriate intervals of the correlation of the signal. To minimize the time for initial synchronization, the signal should be changed so that the autocorrelation function at each stage to be agreed with the necessary increase in aposteriority density.